HUBUNGAN POLA KOMUNIKASI KELUARGA CONVERSATION ORIENTATION DENGAN PSYCHOLOGICAL WELL-BEING PADA REMAJA DI KOTA AMUNTAI UTARA - Maulida Rahmah; Aziza Fitriah; Ghea Amalia Arpandy (Jurnal Gesi, 2023)
Psychological well-being is an individual's ability to accept himself, to be able to establish relationships withother people, to be a person who is independent from social pressure, to be able to control areas outside ofhimself, to have meaning in his life, and to realize his potential continuously. Establishing a good relationshipwith parents is an important factor in improving Psychological Well-Being. Healthy family communicationpatterns and conversion orientation are key elements for building good relationships and enhancing thepsychological well-being of adolescents. The purpose of this study was to determine the relationship betweenconversion-oriented family communication patterns and the psychological well-being of adolescents in the city ofAmuntai. Quantitative research methods with correlation studies. A sample of 219 adolescents in Amuntai City inJune and July 2023 was taken using an accidental sampling technique. Data were analyzed using the sparmanrho test. The results showed that there was a significant relationship between family communication patterns,conversion orientation and adolescent psychological well-being in Amuntai City, with a p-value (0.019<0.05), r =0.159.Keywords: Family Communication Convertatin Orientation, Psychological Well-Being, Teenager